Ion synthesis of iron granular films in polyimide - Khaibullin, RI; Popok, VN; Bazarov, VV; Zheglov, EP; Rameev, BZ; Okay, C; Tagirov, LR (Elsevier Science Bv, 2002)
40 keV Fe+ ions were implanted into polyimide (PI) films with doses of (0.25-1.25) x 10(17) ions/cm(2) at ion current densities of 4, 8 and 12 muA/cm(2). Transmission electron microscopy study showed that iron granular films consisting of isolated metal particles with lateral sizes of 25-300 run were formed in the irradiated (carbonised) layer of polymer. An influence of implantation parameters and thermal annealing on magnetic properties of the synthesised iron films was investigated by the ferromagnetic resonance technique. It was found that the metal/polymer composite layer is formed at highest dose of 1.25 x 10(17) ions/cm(2) and it reveals the characteristics of a continuous magnetic film: remanent magnetisation and coercive field. (C) 2002 Elsevier Science B.V. All rights reserved.
11th International Conference on Radiation Effects in Insulators -- SEP 03-07, 2001 -- LISBON, PORTUGAL
Keywords: ion implantation; polyimide; magnetic granular films; nanostructured magnetic materials